2022
DOI: 10.1101/2022.02.01.478743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scale of analysis drives the observed ratio of spatial to non-spatial variance in microbial water quality: insights from two decades of citizen science data

Abstract: While fecal indicator bacteria (FIB) testing is used to monitor surface waters for potential health hazards, recent studies report substantial variation in FIB levels and that observed variation appeared dependent on scale of analysis (SOA). Citizen science data and random effects models were used to quantify variance in FIB levels attributable to spatial versus temporal factors. Separately, Bayesian models were used to quantify the ratio of spatial to nonspatial variance in FIB levels, and identify associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…A 2020 review of agricultural water in the Southeastern United States noted that the geographical location of a water source played an important role in the prevalence and survival of foodborne pathogens ( 35 ). This conclusion is supported by other studies that compared microbial water quality between growing regions nationally ( 16 , 37 ) and locally ( 12 , 17 , 38 ), and between water types ( 32 , 39 41 ). Indeed, multiple studies have shown that this variability in water quality limits the efficacy of one-size-fits-all approaches to monitoring and mitigating microbial hazards in aquatic environments.…”
Section: Introductionsupporting
confidence: 76%
“…A 2020 review of agricultural water in the Southeastern United States noted that the geographical location of a water source played an important role in the prevalence and survival of foodborne pathogens ( 35 ). This conclusion is supported by other studies that compared microbial water quality between growing regions nationally ( 16 , 37 ) and locally ( 12 , 17 , 38 ), and between water types ( 32 , 39 41 ). Indeed, multiple studies have shown that this variability in water quality limits the efficacy of one-size-fits-all approaches to monitoring and mitigating microbial hazards in aquatic environments.…”
Section: Introductionsupporting
confidence: 76%
“…Datasets. This study used historical data from 16 peer-reviewed papers and two citizen science databases where the original source was willing to share the complete dataset (12,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Specifically, we compiled data from the Northeastern USA that reported (i) the presence or absence of foodborne pathogens in soil, water, vegetation, or wildlife feces, or (ii) dissolved oxygen, fecal indicator bacteria, chloride, conductivity, nutrient, salinity, or sediment levels in streams.…”
Section: Survey and Streammentioning
confidence: 99%
“…Data were available on water quality outcomes from published studies (32)(33)(34) and citizen science datasets, including outcomes with food safety implications [e.g., fecal indicator bacteria (FIB) levels]. Several of the water quality datasets [e.g., (35)(36)(37)] overlap spatially and temporally with surveys that tested farm and other environmental samples for foodborne pathogens [e.g., (12,32,(38)(39)(40)]. Since we compiled datasets from multiple sources, it was important to determine if methodological differences between datasets would swamp signals of interest.…”
Section: Introductionmentioning
confidence: 99%